The Influence of Husband Support and Parity Against the Incidence of Drop Out of 3 Monthly Injection Contraception in Pamekasan - Nova Purma Hardini; Yuly Peristiowati; Byba Melda Suhita (Health Notions, 2018)
Rapid population growth in Indonesia has prompted the government to launch the Family Planning program in order to reduce the birth rate. This research was conducted to find out what factors influenced the incidence of drop out of 3 monthly injection contraception in Pamekasan and analyzed the most dominant factor on the incidence of drop out of 3 monthly injection contraception at Proppo Health Center, Pamekasan. The research design in this research was analytical survey with cross sectional approach. Population in this research was all acceptor drop out of 3 monthly injection 3 month contraception in Pamekasan. The sample size was 149 people, selected by cluster sampling. The analysis technique used was ordinal regression analysis using SPSS v.23 for Windows. The dominant factor on the incidence of drop out of 3 monthly injection contraception in Pamekasan was husband support. Keywords: husband support; knowledge; incidence of drop out of 3 monthly injection contraception